STUDI KELAYAKAN PENGEMBANGAN KLINIK UTAMA MATA MITRA MEDIKA BANDUNG - Fransiskus Dicky Septiawan,; Bayu Wahyudi,; Kahar Mulyani, (Journal of Innovation Research and Knowledge, 2025)
The increasing demand for eye healthcare services in Bandung presents a strategic opportunity for the development of more comprehensive healthcare facilities. This study aims to evaluate the feasibility of establishing the Mitra Medika Eye Clinic in Bandung by analyzing the marketing, human resources, legal, financial, and environmental impact aspects. This research employs a business feasibility study method utilizing qualitative approach. The findings indicate that, from a marketing perspective, there is significant market potential driven by the rising public awareness of eye health. In terms of human resource, the limited availability of ophthalmology specialists poses a challenge, however, this can be addressed through effective recruitment strategies and ongoing professional development programs. From a legal perspective, the establishment of the clinic must comply with strict licensing requirements and healthcare service standards. Financial analysis indicates promising profitability, contingent on effective cost management. From an environmental perspective, mitigating ecological impacts, particularly in medical waste management and resource efficiency, are crucial for ensuring the clinic’s sustainable operations. Based on these findings, the development of the Mitra Medika Eye Clinic in Bandung is deemed feasible, provided that a comprehensive strategic plan is implemented to ensure its competitiveness and long-term sustainability in the healthcare sector